Mustak (Cyperus Rotundus Linn.) is a Good Remedy Against ‘Atisar’ (Diarrhoea): An Ayurvedic Literary Review - Mukhopadhyay, Rupa; Karmahapatra, P B (International Research Journal of Ayurveda & Yoga, 2022)
In Ayurveda, Atisar, has been defined as a condition where constant oozing out (Ati and sarana) of the liquid fecal matter from the anus. This condition is more or less similar to the sense of diarrhoea in western view. There are several anti-amoebic an anti diarrhoeal drugs are frequently used by the allopathic physicians for prevention and control of the diseases. But those are having several adverse effects. From ancient era to till date Ayurveda has also contributed a lot of ‘Atisernasak’ (antidiarrhoeal / antiameobic) herbs and compound medicine. ‘Mustak’ (Cyperus rotundas, Linn) is one of the popular antidiarrhoeal remedy has been mentioned in different classical texts. In present study review of Ayurvedic literatures have been done to collect the informations regarding the action of ‘Mustak’ as well as pharmacodyanamics (Rasa, Guna, Virya, Vipak & Dosakarma). Methodical and scientific representation of those information have been furnished here with to justify the claim of Ayurveda that ‘Mustak’ is a good remedy as ‘Atisarnasak’. After being reviewed of the literatures it has been found that ‘Mustak’ cures ‘Atisar’.